Communication patterns of some Afrikaans speaking Coloureds and Whites in the Cape Peninsula - Elirea Bornman; H.J. Groenewald; Elsa Hall (Communicare)
INTERGROUP relations are of the utmost importance in South Africa where these re- lationships have seriously deteriorated dur- ing the past decade. In this study the focus Is on the communication patterns of Afri- kaans speaking Coloureds and Whites In the Cape Peninsula. These two groups share important facets of a common culture and this aspect should be a major impetus for positive communication between them. This approach proved to be rather simplis- tic and therefore attention is given to the social identity theory and the contact hypothesis to explain the data obtained in the pilot study. Although there are some similarities between the two population groups there are also some differences in the communication patterns. Communica- tion between the two groups takes place primarily in the context of the work situa- tion. Because of the relatively small number of respondants involved in the study no generalized conclusions could be made. It seems, however, that the relationships of different groups of people in a multicultural society will not improve as long as certain measures exist in the society to treat them as totally different entities with different needs and aspirations. This aspect was dis- cussed in depth in the theoretical founda- tion of the study.